PENYUSUNAN PETA ADMINISTRASI BERBASIS SISTEM INFORMASI GEOGRAFIS PADA DESA PENFUI TIMUR KECAMATAN KUPANG TENGAH KABUPATEN KUPANG PROVINSI NTT - Manubulu, Christiani Chandra; Bela, Krisantos R.; M. F. Seran, Sri Santi L.; Amasan, Alfred Jejenus; Alfuara Tedu, Nomentius (LPPM Universitas Bina Bangsa, 2024)
In order to realize the Sustainable Development Goals (SDGs), the Ministry of Villages, Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia (Kemendes PDTT) reduce the National SDGs to become Village SDGs. The Village SDGs are an integrated effort to realize the achievement of sustainable national development goals or national SDGs. With the intention that this goal can be planned and implemented well, naturally each village/district must prepare an activity plan in carrying out development, including the need for an initial study and inventory of the potential possessed by a village, and this can be done by presenting it in the form of a basic map. Knowing that East Penfui Village does not yet have a suitable regional boundary map, this service activity can produce a Geographic Information System-based village boundary map that is appropriate to the actual situation, so that it can be used by the village government or other parties if needed at any time